MEASURES FOR ADAPTATION OF IN VITRO PROPAGATED MULBERRY VARIETIES TO EXTERNAL CONDITIONS - Mirzaeva Yorkinoy Yarkulovna; M.F. Kuziboeva; J. G. Zhavliev (Galaxy International Interdisciplinary Research Journal, 2021)
The significance of the experimental results of the multiplication of mulberry varieties in vitro and the recommendations of some researchers in this area, as well as the calculations of the annual production of a product in the production program, obtained as a result of experiments in natural and value terms.